2005
DOI: 10.1071/fp05091
|View full text |Cite
|
Sign up to set email alerts
|

Integrated responses of rosette organogenesis, morphogenesis and architecture to reduced incident light in Arabidopsis thaliana results in higher efficiency of light interception

Abstract: Plants have a high phenotypic plasticity in response to light. We investigated changes in plant architecture in response to decreased incident light levels in Arabidopsis thaliana (L.) Heynh, focusing on organogenesis and morphogenesis, and on consequences for the efficiency of light interception of the rosette. A. thaliana ecotype Columbia plants were grown under various levels of incident photosynthetically active radiation (PAR), with blue light (BL) intensity proportional to incident PAR intensity and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 30 publications
3
47
1
Order By: Relevance
“…In all accessions, the decrease in leaf expansion rate caused by water deficit was at least partly compensated for by an increase in the duration of leaf expansion. Opposite effects of environmental changes on the rate and duration of leaf expansion have been shown previously in A. thaliana plants subjected to different temperatures (Granier et al 2002) and reduced incident light (Chenu et al 2005;Cookson & Granier 2006). This phenomenon is also well known for temperature response in many plants (Granier & Tardieu 1998 on sunflower).…”
Section: Underlying Leaf Growth Variables Have Different Sensitivitiementioning
confidence: 87%
“…In all accessions, the decrease in leaf expansion rate caused by water deficit was at least partly compensated for by an increase in the duration of leaf expansion. Opposite effects of environmental changes on the rate and duration of leaf expansion have been shown previously in A. thaliana plants subjected to different temperatures (Granier et al 2002) and reduced incident light (Chenu et al 2005;Cookson & Granier 2006). This phenomenon is also well known for temperature response in many plants (Granier & Tardieu 1998 on sunflower).…”
Section: Underlying Leaf Growth Variables Have Different Sensitivitiementioning
confidence: 87%
“…5b, d), the same kind of response leaf photosynthesis shows to intercepted light (Larcher 2003). This kind of logarithmic response of meristematic activity to light absorbed by whole plants had previously been observed for Arabidopsis thaliana by Chenu et al (2005) who interpreted this as a response to assimilate availability in the meristems. Consistently, it has been shown that the amount of photosynthetic products in meristems directly relates to meristematic activity (Smeekens 2000;Pien et al 2001;Freixes et al 2002).…”
Section: Acclimation To High Lightmentioning
confidence: 75%
“…5b, d, f) indicating that the increments in photosynthesis with increasing amount of intercepted light no longer persists for high light transmittance levels. As previously discussed, photoinhibition may partly explain these results through its effect of depressing photosynthesis (Powles 1984) and hence plant growth (Ö gren and Sjö strö m 1990; Winter and Kö nig 1991;Liang et al 1995;Werner et al 2001) and assimilate availability in meristems (Chenu et al 2005). Another part of this effect of high light may be related to changes in leaf temperature induced by light transmittance.…”
Section: Acclimation To High Lightmentioning
confidence: 92%
“…Archimed is a simulation platform gathering biophysical models, including radiative models previously described by Dauzat and Eroy (1997) and by Chenu et al (2005). The principle of the simulations lays on numerical computation of directional radiative intercepted fluxes on virtual trees.…”
Section: Models Usedmentioning
confidence: 99%